Students' perception of diversity in an international classroom - Loïse Jeannin (Laureate Education Inc, 2013)
This paper presents students' perception of diversity in an international classroom in one international university in Thailand. The aim of this exploratory study is to better understand students' perception of diversity to better meet their learning needs. By conducting a survey among students enrolled in bachelor's and master's international programs, this study explores how students perceive their classmates' diversity, such as, but not limited to, cultural, language, and knowledge differences. How does diversity affect students' learning in an international setting? What kind of diversity is the most disturbing for learners? Some recommendations grounded in the conceptual framework of cultural responsive teaching are derived from the results. DOI: http://dx.doi.org/10.18870/hlrc.v3i4.165